The influence of chemical surface modification of kenaf fiber using hydrogen peroxide on the mechanical properties of biodegradable kenaf fiber/poly(lactic acid) composites - Abdul Razak, Nur Inani; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Rayung, Marwah; Saad, Wan Zuhainis (MDPI, 2014)
Bleaching treatment of kenaf fiber was performed in alkaline medium containing hydrogen peroxide solution maintained at pH 11 and 80 °C for 60 min. The bleached kenaf fiber was analyzed using Fourier Transform Infrared (FTIR) and X-ray Diffraction (XRD) analysis. The bleached kenaf fiber was then compounded with poly-(lactic acid) (PLA) via a melt blending method. The mechanical (tensile, flexural and impact) performance of the product was tested. The fiber treatment improved the mechanical properties of PLA/bleached kenaf fiber composites. Scanning electron micrograph (SEM) morphological analysis showed improvement of the interfacial adhesion between the fiber surface and polymer matrix.